COMMUNICATION IN THE MAHACHAT SERMON TO PROMOTE CITIZENSHIP IN DEMOCRACY - Liohprasert, Phramaha Pongthep; Panyarvuttrakul, Hareuthai; Sridee, Supaporn; Ngamsanit, Sman (Journal of Social Science and Cultural, 2024)
The objectives of this research were to study communication to promote democratic citizenship via the Mahachat sermon in terms of 1) content and messages in the sermon; 2) method of presentation; and 3) approaches for improving the messages, content and presentation style to further promote good citizenship in a democracy. This research used the qualitative research method of in-depth interviews. There were 20 key informants, consisting of Buddhist monks who had experience in giving the Mahachat sermon; lay people who had listened to the Mahachat sermon; and academic experts with experience in the fields of communication arts and religion. The key informants were chosen by purposive sampling. The data collection instruments were an in-depth interview form and a focus group discussion form. Data were analyzed by drawing conclusions. The results showed that 1) For content, there were 4 main dimensions: 1.1) in the physical dimension, monks could use the content of the 13th chapter (Nakorngan) to transmit ideas intended to mold listeners’ knowledge, attitudes and behavior to be more fitting for citizens in a democracy; 1.2) in the social dimension, monks could use the content in the first chapter (Tosaporn) to transmit the ideals of responsibility, honesty, and being a law-abiding citizen; 1.3) in the emotional dimension, monks could use content in the second chapter (Himaphan) to transmit conscientiousness about being a Thai citizen, being just, and having a civic sense of self-sacrifice for the common good; and 1.4) in the intellectual dimension, monks could use content in the 6th chapter (Julaphon) to transmit ideas about the importance of analytical thinking, evidence-based rational problem-solving, and participating in politics and administration using only peaceful means. 2) For presentation methods, monks would normally 2.1) start by introducing the audience to the subject by relating the origins of the Mahachat sermon and its story; (2) tell the story using their tone of voice, gestures, and cadence to bring out both the good and bad sides of each character, to arouse listeners’ emotions and encourage them to see the truth and beauty of the dharma teachings, to really enjoy the story while listening, and to gain lessons they can then put to use in their daily lives; 2.3) summarize the lessons, give good take-home conclusions from the tale, and conclude with memorable new definitions and key phrases. 3) For suggestions for improving the content and methods of preaching via the Mahachat sermon to promote citizenship in a democracy, a systematic development plan should be implemented to providing accurate knowledge of Buddhist principles, integrating modern media, and leveraging the role of temples as community centers.